Estudios y diseños del sistema de agua potable y saneamiento del barrio Chinguilamaca del cantón Gonzanamá, provincia de Loja. - Flores González, Diego Alejandro. (2015)
This work order titling, and argues describes the processes required to design a system of water supply and sanitation applied to Chinguilamaca Purunuma neighborhood parish, Canton Gonzanamá, Province of Loja. The different units projected in the system have as a starting point preliminary studies of topography, demographic study, soil survey, analysis of water quality at the source, capacity, environmental impact study and financial evaluation. In this thesis topic consulting the results of design units is presented at different stages of the water supply system, reporting the design of the collection, pretreatment units, pipeline, treatment plant networks distribution and ancillary works. With regard to sanitation has adopted a Basic Health Unit for excreta disposal, consisting of a latrine and wastewater treatment. The work described above theoretically solve the pressing needs of vital fluids and proper disposal after use, improving the quality of life and ensuring a comprehensive development